2022
DOI: 10.3390/ijms23031869
|View full text |Cite
|
Sign up to set email alerts
|

Cold Exposure Drives Weight Gain and Adiposity following Chronic Suppression of Brown Adipose Tissue

Abstract: Therapeutic activation of thermogenic brown adipose tissue (BAT) may be feasible to prevent, or treat, cardiometabolic disease. However, rodents are commonly housed below thermoneutrality (~20 °C) which can modulate their metabolism and physiology including the hyperactivation of brown (BAT) and beige white adipose tissue. We housed animals at thermoneutrality from weaning to chronically supress BAT, mimic human physiology and explore the efficacy of chronic, mild cold exposure (20 °C) and β3-adrenoreceptor ag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
1
1
Order By: Relevance
“…Our data contrast the observations in rats kept until 12 weeks old at 28 °C and then transferred for 4 weeks to 20 °C [ 88 ]. In that study there was a suggested increase in adiposity, the opposite of our observation of decreased adiposity coincident with declining temperatures.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our data contrast the observations in rats kept until 12 weeks old at 28 °C and then transferred for 4 weeks to 20 °C [ 88 ]. In that study there was a suggested increase in adiposity, the opposite of our observation of decreased adiposity coincident with declining temperatures.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the sample size in that study was small (two temperature exposure groups with n = 6 per group) and there were no discernible impacts of the temperature manipulation on either food intake or energy expenditure, indicating the exposure did not take the rats outside their thermoneutral zone when ‘cold exposed’. Moreover, while increased adiposity was mentioned in the title and abstract of the paper, the increase in total adipose tissue in the cold was not significant ( Figure 2 C in ref [ 88 ], p = 0.0532).…”
Section: Discussionmentioning
confidence: 97%